Traffic Flow Characteristics with Transportation Plans Components - Baričević, Hrvoje; Dundović, Čedomir (Promet - Traffic&Transportation, 2012)
Knowledge of traffic characteristics is useful to the highwayengineer in developing highway and transportation plans, performingeconomic analyses, establishing geometric design criteria,selecting and implementing traffic control measures, andevaluating the pe1[ormance of transportation facilities. Doze/ISof measures have been employed to describe the quality andquantity of traffic flow. This paper presents information onthose flow characteristics that fundamentally bear on the planning,design, and operation of highway and transport facilities:traffic speed, travel time, volume, and density.